Effect of forward head posture on thoracic shape and respiratory function - Koseki, Taiichi (J Phys Ther Sci, 2019)
[Purpose] This study investigated the effect of forward head posture on upper and lower thoracic shape in adults to better understand the relationship between a forward head posture and respiratory function. [Participants and Methods] Fifteen healthy males were recruited after obtaining informed consent from all participants. All participants were instructed to respire in both the forward and neutral head postures while seated. Respiratory function was assessed using spirometry. Thoracic shape during respiration was assessed using 23 markers on both the upper and the lower thorax and compared between the 2 postures. [Results] Forced vital capacity, expiratory and inspiratory reserve volumes, forced expiratory volume at 1 second, and the peak flow rate observed with the forward head posture were significantly lower than that with the neutral head posture. The upper thorax showed a greater forward shift and the lower thorax showed a greater forward and inward shift with the forward head posture than with the neutral head posture. No significant difference in upper thoracic mobility was observed during respiration between the forward head posture and the neutral head posture. However, mobility of the lower thorax during respiration was significantly reduced with the forward head posture. [Conclusion] The forward head posture causes expansion of the upper thorax and contraction of the lower thorax, and these morphological changes cause decreased respiratory function.